2015
DOI: 10.1007/s11250-015-0768-9
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with occurrence of African swine fever outbreaks in smallholder pig farms in four districts along the Uganda-Kenya border

Abstract: A cross-sectional survey was carried out to assess risk factors associated with occurrence of African swine fever (ASF) outbreaks in smallholder pig farms in four districts along Kenya-Uganda border. Information was collected by administering questionnaires to 642 randomly selected pig households in the study area. The study showed that the major risk factors that influenced ASF occurrence were purchase of pigs in the previous year (p < 0.000) and feeding of pigs with swill (p < 0.024). By employing cluster an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
66
0
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 13 publications
8
66
0
3
Order By: Relevance
“…The lack of biosecurity and related continuous circulation of ASF in smallholder settings in endemic areas thus creates a biosecurity challenge for enterprises that aspire at larger-scale pig farming in these areas. In smallholder settings in endemic areas, outbreaks of ASF, like other diseases, are largely under-reported (de Balogh et al 2013; Chenais et al 2015a; Nantima et al 2015). As a consequence, the progression of outbreaks and the related impacts are seldom described in detail.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of biosecurity and related continuous circulation of ASF in smallholder settings in endemic areas thus creates a biosecurity challenge for enterprises that aspire at larger-scale pig farming in these areas. In smallholder settings in endemic areas, outbreaks of ASF, like other diseases, are largely under-reported (de Balogh et al 2013; Chenais et al 2015a; Nantima et al 2015). As a consequence, the progression of outbreaks and the related impacts are seldom described in detail.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, producers are reluctant or unable to invest in improving management by confining their pigs, feeding them on commercial rations and providing basic health care (Lekule & Kyvsgaard, ; Penrith et al., ; Verhulst, ). The risks posed by feeding pigs garbage, either as swill or by releasing them to scavenge, and by selling pigs through agents who move from farm to farm, are compounded by panic selling of pigs and infected pork during outbreaks of ASF, which serves to spread the disease (Brown et al., ; Chenais, Boqvist, Sternbgerg‐Lewerin, et al., ; Dione, Ouma, Opio, Kawuma, & Pezo, ; Dione et al., ; Lichoti et al., ; Muwonge et al., ; Nantima et al., ). A survey of pig sales patterns on the border between Kenya and Uganda revealed that producers selling sick pigs tend to seek markets in communities further away from their usual outlets (Lichoti et al., ).…”
Section: Transmission Routes Of Asfv In Domestic Cyclesmentioning
confidence: 99%
“…Recent studies have identified a number of risk factors that contribute to in‐country maintenance and spread of ASF. These include presence of slaughter facilities/home slaughter in pig farming communities, indiscriminate disposal of pig viscera and waste materials after slaughter, presence of an infected pig farm in the neighbourhood, uncontrolled access to pigs by farm‐gate buyers collecting pigs and pig products from within farms and veterinarian/paraveterinarians during outbreaks without observance of strict biosecurity, that is, poor implementation of biosecurity measures, salvage sale of survivor and apparently healthy pigs without testing, continuous maintenance of sick and survivor pigs in the herd and delayed response by the veterinary authorities to respond to outbreaks (Dione et al., ; Fasina, Lazarus, Spencer, Makinde, & Bastos, ; Fasina, Agbaje et al., ; Kabuuka et al., ; Muhangi et al., ; Nantima et al., ). Permanent confinement of pigs and exercise of reasonable levels of biosecurity protected farmers from ASF, according to a study on pig production in south‐eastern Nigeria (Nwanta et al., ).…”
Section: Risk Factors Implicated In Maintenance and Spread Of Asfmentioning
confidence: 99%